Learning Media for Islamic Religious Education during a Pandemic: Systematic Literature Review Analysis - Asdlori Asdlori (International Journal of Social Science and Religion (IJSSR), 2023)
This study intends to analyze the learning media utilized for Islamic religious education in Indonesia during the Covid-19 pandemic. This study is a systematic literature review utilizing the Prisma methodology. Mendeley and Garuda article databases with limited articles published from 2020 to 2023 are utilized. Using the search terms "Islamic religious education, learning media, covid, pandemic", 53 articles were located. Utilizing field research and accepting only journal articles made it possible to include data. Consequently, only twenty articles were examined. The Phillips Marrying content analysis technique was used for data analysis. Coding data with the Atlas.ti application. The results of the study indicate that the types of learning media utilized during the pandemic are synchronous and asynchronous. Jitsi Meet, Google Meet, Zoom, and Microsoft Teams are examples of synchronous learning media. The asynchronous media utilized are learning management systems such as e-learning in educational institutions, Google Classroom, and Edmodo, as well as other supporting media such as Google Forms, Kahoot, Quizziz, Microsoft PowerPoint, YouTube, and videos. During a pandemic, there were several issues with the use of internet-based learning media, including inadequate devices, poor internet infrastructure, and the inability of students' parents to pay. The use of learning media for distance education must take several factors into account for learning to proceed smoothly.